PERAN BADAN USAHA MILIK DESA ( BUM DESA) DALAM MEMBERDAYAKAN PETANI VANILI(vanilla planifolia) DI DESA LUBA KECAMATAN LEMBUR, KABUPATEN ALOR - Ade Suryani; Mustafa Abdurrachman; Charles Kapioru (Buletin Ilmiah Impas, 2021)
The problems faced by Vanilla Farmers are the lack of services from economic institutions established by the Government in developing productive economic enterprises in the village and the lack of availability of various aspects of community empowerment that affect the income and economic welfare of vanilla farmers.The research method is descriptive qualitative using a Likert scale, to measure the attitudes, opinions and perceptions of a person or group of social phenomena with an ordinal scale. The research location is in Luba Village, Lembur District, Alor Regency. The data collection techniques are interviews, observation, and documentaries. Research objectives: (1) Knowing the Role of Village-Owned Enterprises in Empowering Vanilla Farmers (2) Knowing what are the obstacles of Village-Owned Enterprises in Empowering Vanilla Farmers, and (3) Knowing the success of Village-Owned Enterprises in Empowering Vanilla Farmers. The role of BUM Desa then has an impact on the attributes of community empowerment, including Human Development, Business Development, Environmental Development and Institutional Development. The results of the study are (1) The role of BUM Desa socially and economically for vanilla farmers by taking into account several dimensions of empowerment, including Human Development, Business Development, Environmental Development and Institutional Development, the results obtained were 53.77% BUM Desa in the category Enough Role in empowering farmers. vanilla. This result has not been maximized because several aspects in the context of empowerment have not been maximally played by BUM Desa. (2) The obstacles to empowering vanilla farmers include the lack of development of training and routine meetings, inequality of facilities and infrastructure to support the vanilla business, the lack of environmental conservation activities, the distribution of business capital has not yet been implemented so that it has not been utilized by vanilla farmers. (3) The Village Government should further increase capital participation in Village-Owned Enterprises (BUM Desa) sourced from Village Funds, to develop their BUM Desa business units.